Collagen quantification in rabbit dermal wounds treated with heterologous platelet-rich plasma gel - Marques, Maria Elisa Marin; Laposy, Cecília Braga; Dos Santos Silva, Mariana Lucas; Breda, Maria Rosa Santos; Matsumoto, Mayara Mascaro; Junior, Luis Antonio Justulin [UNESP]; Nai, Gisele Alborghetti; Osaki, Guilherme Akio Tamura [UNESP]; Filho, José Carlos Camargo [UNESP]; Nogueira, Rosa Maria Barilli (Universidade Estadual de Londrina, 2017)
Platelet-rich plasma (PRP) has been extensively studied as a biomaterial for wound treatment, and the heterologous PRP is usefulin the event that obtaining the patient's own blood is impossible. This study aimed to evaluate and compare wound healing in rabbits and quantify the collagen in experimentally induced wounds in a control group and in a group treated with heterologous PRP gel. We hypothesize that this gelis capable of promoting proper healing with no adverse reactions, increased collagen content. The clinical aspects of coloring, edema, hyperemia, exudation, crust, granulation, pain sensitivity, and retraction index of the wounds were measuredon days 7, 14, and 17 after the injury. Collagen quantification by Picrosirius staining and evaluation under polarized light was performed on the 17th day. Crust was present in both groups at all evaluated time points, with the absence of other clinical signs. The wound contraction rate and collagen quantity did not differ between groups. In conclusion, the suggested hypothesis was partially confirmed; the heterologous PRP gel was unable to increase the amount of collagen and accelerate the wound healing process, however, wound healing was efficient and similar in both groups and there was no local adverse reaction. Thus, despite the scarcity of studies in the literature, the heterologous PRP gel is an effective alternative treatment for wounds in the absence of other sources of PRP.
Keywords: Collagen; Platelet-rich plasma; Rabbits; Wound healing